2000
DOI: 10.1046/j.1365-2133.2000.03658.x
|View full text |Cite
|
Sign up to set email alerts
|

The A5.1 allele of the major histocompatibility complex class I chain-related gene A is associated with psoriasis vulgaris in Chinese

Abstract: These results suggest that the MICA gene may be associated with the development of PS in Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…For example, MIC molecules have previously been shown to associate with psoriasis. These molecules are in fact recognized by NK/NKT cells as their expression seems to be triggered by low levels of HLA class I expression (Cheng et al, 2000;Dunn et al, 2000). It will therefore be important to determine whether HLA-C and MIC, and perhaps other immune molecules interact in psoriasis pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…For example, MIC molecules have previously been shown to associate with psoriasis. These molecules are in fact recognized by NK/NKT cells as their expression seems to be triggered by low levels of HLA class I expression (Cheng et al, 2000;Dunn et al, 2000). It will therefore be important to determine whether HLA-C and MIC, and perhaps other immune molecules interact in psoriasis pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…HLA-E is a nonclassical class I molecule that provides a ligand for NKG2A/CD94, and NKG2C/CD94 receptors expressed by NK cells, and MICA encodes an antigen expressed in response to stress or particular pathological situations that activates NK cells through ligation of NKG2D [52]. An allele of MICA that possibly encodes for a soluble receptor, termed MICA A5.1, is associated with an increased risk of Psoriasis Vulgaris in a Chinese patient cohort [53]. Although there has been some controversy in the literature [6, 54], it seems likely that HLA-Cw6 constitutes the actual risk variant rather than acting as a marker for a nearby gene that is responsible for the effects seen.…”
Section: Recent Advances In Genetic Analysis Of Psoriasismentioning
confidence: 99%
“…One Australian study found an association between Type I psoriasis and the MICA allele which has nine GCT repeats (A9) and a guanine deletion at the beginning of intron 4 [25]. Other studies in Chinese and Korean patients have shown an association between the truncated form of the protein, A5.1, and Type I psoriasis [26,27]. None of these studies looked for the presence of arthritis complicating the psoriasis.…”
Section: Micamentioning
confidence: 95%